Centro de apoio à mulher - Pereira, Paula Laís Cavalcante (Brasil, 2022)
The research work presented aims to support the architectural proposal of implantation, in the city of Manaus, of a "Women's Support Center", aiming at professional training, assistance in entering the job market, or their autonomy in the search for financial independence. In the same way as, through education, it intends to transform the reality of these women. The intention is to expand the Service Network beyond the prevention and combat of violence, but also for the rescue of women who, through a lot of struggle, managed to break the cycle of violence. Therefore, the proposal is to create a project that can be a support and a place of transformation. For this, it was necessary to carry out documentary research, bibliographic review, survey of data made available by government agencies, and analysis of the same to justify the imminent urgency of intervention in this sense, which becomes even more evident in the context of a pandemic.